Perjanjian Hak Kekayaan Intelektual Asean di Bidang Paten dan Implikasinya bagi Indonesia - Delfiyanti, Delfiyanti (Nagari Law Review, 2025)
Managing Intellectual Property well can help increase revenue streams of businesses and enhance shareholders’ value. As a class of property that includes intangible creation of the human mind, Intellectual Property also protects technology innovations, enhance brand recognition and increase competitive advantage for products and services in the global marketplace. Intellectual Property includes patents, utility models, copyright, industrial designs, trademarks, plant variety protection, integrated circuits design, genetic resources, trade secret, traditional knowledge, geographical indications and domain names. It plays an important role in the achievement of national and regional socio-economic development goals of the ASEAN Economic Community (AEC). It is also a critical tool in encouraging transfer of technology, and stimulating innovation and creativity that will lead to a competitive, innovative, and dynamic ASEAN as envisioned in the AEC Blueprint 2025. Therefore, the States of the ASEAN Region have entered into an intellectual property regulatory agreement through The ASEAN Intellectual Property Rights Action Plan 2016-2025. The ASEAN Intellectual Property Rights Action Plan, thus formulated, will have four strategic goals: (a) A more robust ASEAN IP System is developed by strengthening IP Offices and building IP infrastructures in the region; (b) Regional IP platforms and infrastructures are developed to contribute to enhancing the ASEAN Economic Community; (c) An expanded and inclusive ASEAN IP Ecosystem is developed; and (d) Regional mechanisms to promote asset creation and commercialisation, particularly geographical indications and traditional knowledge are enhanced. In this agreement there are several principles of international law that are then applied by ASEAN countries including Indonesia. Indonesia’s participation in ratifying the ASEAN Charter in 2008 provides binding implications for Indonesia to harmonize legal arrangements. For Indonesia, participation in this agreement will certainly enhance the legal protection of intellectual property in Indonesia.